Towards an ideal tafsir methodology and Sayyid Mawdudi's tafhimul Qur'an - Osmani, Noor Mohammad; Habibur Rahman, Muhammad; Ali, Md. Yousuf (Kolej Universiti Islam Perlis (KUIPS), 2022)
An ideal Qur’anic interpretation lies on interpreting the Qur’an by similar Qur’anic ayat, by the ahadith of the Prophet, by the usage of Arabic language and resorting to one’s sound judgments that is not contradicting with shari`ah principles and maqasid shari`ah, the objectives of Islamic law. Qur’anic interpreters have different approaches to the Qur’anic interpretation. Some of them totally depended on Tafsir al-Ma’thur, or tradition based tafsir; while others depended on Tafsir bi al-Ra’i, or rational interpretation of the Qur’an. Both these schools exceeded the limits to interpret the Qur’an. Traditionist scholars did not allow even a valid rational interpretation, while rationalists preferred their rationality always on even authentic ahadith of the Prophet (PBUH). Sayyid Mawdudi (1903-1979) followed a balanced approach in the interpretation of the Qur’an. He always preferred traditional interpretation of the Qur’an giving top priority to the ayat and ahadith of the Prophet. He also resorted to sound judgments as well in the Qur’anic interpretation without crossing the borders. At the same time, he did not hesitate to disapprove some ahadith of the Prophet, though not many, if it is proven to him, totally against shari`ah and sound mind. The current study is based on the textual analysis of Sayyid Mawdudi’s magnum opus tafsir Tafhim ul Qur’an, and the method he followed therein, to judge if it is suitable to the ideal Qur’anic interpretation, or that is against it. It is observed that Sayyid Mawdudi’s approach to the interpretation of the Qur’an is amongst the ideal methodology of the Qur’anic commentary. He always searched for the truth being within the limits of shari`ah and addressing the modern day problems to suit it to the modern generation of the people.